DNA Dosimetry with Gold Nanoparticle Irradiated by Proton Beams: A Monte Carlo Study on Dose Enhancement - Ngoc Han Huynh (MDPI AG, 2021)
Heavy atom nanoparticles, such as gold nanoparticles, are proven effective radiosensitizers in radiotherapy to enhance the dose delivery for cancer treatment. This study investigated the effectiveness of cancer cell killing, involving gold nanoparticle in proton radiation, by changing the nanoparticle size, proton beam energy, and distance between the nanoparticle and DNA. Monte Carlo (MC) simulation (Geant4-DNA code) was used to determine the dose enhancement in terms of dose enhancement ratio (DER), when a gold nanoparticle is present with the DNA. With varying nanoparticle size (radius = 15–50 nm), distance between the gold nanoparticle and DNA (30–130 nm), as well as proton beam energy (0.5–25 MeV) based on the simulation model, our results showed that the DER value increases with a decrease of distance between the gold nanoparticle and DNA and a decrease of proton beam energy. The maximum DER (1.83) is achieved with a 25 nm-radius gold nanoparticle, irradiated by a 0.5 MeV proton beam and 30 nm away from the DNA.